การจำแนกพันธุ์และการวิเคราะห์ความสัมพันธ์ทางพันธุกรรมของกล้วยไม้สกุลหวายหมู่แคลิสตาด้วยเครื่องหมายสก๊อต - มณีเนตร ฐิตาพร; ธนานันต์ ธีระชัย; ธนานันต์ นฤมล (Thai Journal of Science and Technology, 2019)
Abstract The identification of orchid species based on morphology is difficult and may have a high error rate as the specialist is needed. Therefore, this research used start codon targeted (SCoT) markers to analyze the genetic relationship of 14 species in the genus Dendrobium section Callista. The total of 80 primers was used for screening. Then 12 primers were selected and used to identify all samples. A dendrogram based on polymorphic bands was constructed and used to analyze the relationship among these orchids. The results showed 8 groups of similarity coefficients ranging from 0.14 to 0.63. Keywords: Dendrobium; Callista; genetic relationship; start codon targeted (SCoT)